Simulations mapping the influence of oxygen, extruder residence time, and mechanical shear on low-density polyethylene structure during recycling. (16th January 2023) - Yaghini, Nazila; den Doelder, Jaap
Abstract: We present a computational study of the development of structural properties for recycled low-density polyethylene (LDPE). First, we apply the population balance method together with the method of moments to study the mutual influences of scission and crosslinking reactions. Then, we study the combined effects of extruder residence time and oxygen concentration as the initiator of thermo-mechanical degradation in the recycling process of LDPE in a twin-screw extruder. Further, we extend the models to study the influence of mechanical scission. We explore various case study scenarios to incorporate the effect of extruder residence time and mechanical shear. It is concluded that the competition between random scission and crosslinking, as well as the presence of oxygen, play important roles in the degradation of LDPE during recycling. Random scission is a key factor in terms of altering molecular weight distribution (MWD) during a recycling extrusion process. The various explored scenarios with mechanical scission demonstrate the sensitivity of molecular structure to the combination of competing mechanisms during recycling. Graphical abstract: a)Dead chains distribution and b) Average number of branch points per chain length from the deterministic modeling with topological scission, termination by combination, crosslinking and mechanical scission for recycled LDPE. Image 1 Highlights: Simulation methods enable computation of polymer topology changes during extrusion. Mechanical scission affects structure of recycled LDPE in interaction with other effects. Competing mechanisms during recycling show that scission is key for MWD changes.